CRISPR-mediated optogene expression from a cell-specific endogenous promoter in retinal ON-bipolar cells to restore vision - Maddalena, A.; Kleinlogel, S. (Frontiers in Drug Delivery, 2023)
Retinitis pigmentosa, an inherited form of retinal degeneration, is characterized by a progressive loss of rods and subsequent degeneration of cones, leading to blindness. However, the remaining neural portion of the retina (bipolar and ganglion cells) remains anatomically and functionally intact for an extended time. A possible treatment to restore the light sensitivity of the retina consists of rendering the remaining retinal cells photosensitive using optogenetic tools like, for example, Opto-mGluR6, a light-sensitive mGluR6 receptor. We have previously demonstrated that AAV vector-mediated expression of Opto-mGluR6 in ON-bipolar cells restores visual function in otherwise blind mice. However, classical gene supplementation therapy still suffers from high off-target expression rates and uncontrollable target gene expression levels that may lead to either cytotoxicity or lack of functional restoration. To address these issues and achieve cell-specific and endogenously controlled Opto-mGluR6 expression, we employed the CRISPR/Cas technology—in particular, homology-independent targeted integration (HITI) and microhomology-dependent targeted integration (MITI)—to knock-in the Opto-mGluR6 gene behind the ON-bipolar cell-specific GRM6 promoter. We compared four Cas systems in vitro and show that SpCas9 for HITI and LbCpf1 for MITI are well suited to promoting knock-in. As AAV2-mediated ON-bipolar cell transduction resulted in inefficiency, we evaluated Exo-AAVs as delivery vehicles and found Exo-AAV1 efficient for targeting ON-bipolar cells. We demonstrate that intravitreal injection of Exo-AAV1 carrying vectors that promote MITI significantly improved visual acuity in otherwise blind rd1 mice. We conclude by confirming and providing a qualitative evaluation of the MITI-mediated knock-in in the correct genomic locus.